The venous anatomy of the abdominal wall for Deep Inferior Epigastric Artery (DIEP) flaps in breast reconstruction - Rozen, Warren M (AME Publishing Company, 2012)
BACKGROUND: Despite improving outcomes, venous problems in the harvest of deep inferior epigastric artery perforator (DIEP) flaps remain the more common vascular complications. However, it is apparent that the venous anatomy of the anterior abdominal wall has not been described to the same extent as the arterial anatomy. Cadaveric dissection studies of venous anatomy frequently lack the detail of their arterial counterparts. Venous valves complicate retrograde injection, resulting in poor quality studies with limited anatomical information. METHODS: The current manuscript comprises a review of the literature, highlighting key features of the anatomy of the venous drainage of the abdominal wall integument, with particular pertinence to DIEP flaps. Both cadaveric and clinical studies are included in this review. Our own cadaveric and in-vivo studies were undertaken and included in detail in this manuscript, with the cadaveric component utilizing direct catheter venography and the in-vivo studies were undertaken using preoperative computed tomographic angiography (CTA), mapping in-vivo venous flow. RESULTS: Several key features of the venous anatomy of the abdominal wall render it different to other regions, and are of particular importance to DIEP flap transfer. CONCLUSIONS: The cause of venous compromise is multi-factorial, with perforator diameter, midline crossover, and deep-superficial venous communications all important. Venous cadaveric studies as well as clinical CTA preoperatively can identify these anomalies.